Huntington’s disease and HD-like disorders - Tabrizi, Sarah (Henry Stewart Talks, 2014)
Huntington’s disease, Huntington’s disease like disorders, Chorea, Anticipation, Pathobiology of Huntington’s disease, Huntingtin protein misfolding, Aggregation, Ubiquitous expression including in peripheral tissues -Juvenile Huntington’s disease/Westphal variant, Psychiatric, behavioural and cognitive symptomatology, HD phenocopies, C9Orf72 and SCA17